Lactate down‐regulates matrix systhesis and promotes apoptosis and autophagy in rat nucleus pulposus cells. Issue 2 (25th October 2013) - Wu, Wei; Zhang, Xiaolei; Hu, Xuqi; Wang, Xiangyang; Sun, Liaojun; Zheng, Xuhao; Jiang, Libo; Ni, Xiao; Xu, Cong; Tian, Naifeng; Zhu, Siping; Xu, Huazi
ABSTRACT The intervertebral disk (IVD) is avascular and anaerobic glycolysis has been recognized as the main source of energy. Due to anaerobic glycolysis, there are high levels of lactate production in disk. Previous study shows lactate concentration is elevated in the degenerated IVD. However, it is not clear how lactate causes degeneration of disks. In this study, we found that 2 mM lactate promote proliferation of NP cells, while 6 mM lactate slightly inhibit their proliferation. By detection under transmission electron microscopy, and western bolt for autophagy related protein beclin‐1, LC3 and p62, we demonstrated that 6 mM lactate leads to autophagy induction of NP cells. TUNEL results showed that the apoptosis incidence was increased. High lactate concentration induced the degradation in protein expression and mRNA level of GAG content, type II collagen and slight increase of type I collagen. Based on these observations, we conclude that high lactate concentration is a pathogenic factor for IVD degeneration, and lactate metabolism may be a new therapeutic target for IVD degeneration. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:253–261, 2014.